Approaches to Assessing Context and Culture in International Nutrition Education Programs - Keriann H. Paul; Rebecca J. Stoltzfus; Rosemary S. Caffarella (Adult Education Research Conference, 2010)
The purpose of this paper is to explore how context and culture affected the nutrient intakes and complementary feeding (process of feeding solid foods in addition to breast milk) practices of 6 to 12 month old infants in sub-Saharan Africa to generate appropriate nutrition education approaches.